Evolution of Ivorian Popular Front in the Political System of Côte d’Ivoire - SHIPILOV Alexander Yurievich (Ученые записки Института Африки Российской академии наук)
The matter of political leadership in West African countries affected by conflicts and instability is significant in terms of its institutionalisation through political parties and organisations. The article seeks to examine the extent to which the formal political structure and functioning of a party reflect the actual political organisation mechanisms enacted in the fragile institutional environment in the context of civil wars, interethnic violence based on the case of Côte d’Ivoire, especially in the wake of the Ivorian Civil War of 2002-2011. A particular political organisation under examination is the Ivorian Popular Front, created by the former Ivorian President Laurent Gbagbo and the ruling party in Côte d’Ivoire in 2000-2011. A special attention in the framework of this analysis is drawn to the issue of the ethnic and tribal basis of the political party emergence and the significance of this ethnic (religious, regional or any other identity-based) agenda for further development of the political force and its practical operations. Further analysis is devoted to the role of a leader, in this case, Laurent Gbagbo, and the formal and informal patronage networks that emerge surrounding him, the way his political choices reflect identity-based agenda or his personalised interests. Limitations imposed by a political force in a conflict-ridden West African environment are examined both in conditions of control of power over the state and after its loss. A separate question addressed is the matter of a party’s ability to exist without being a dominant political force and a strong connection to the person of its founder and is there an opportunity for a political force that suffered a severe military defeat to return to prominence.